2016
DOI: 10.1186/s13059-016-0950-z
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous profiling of transcriptome and DNA methylome from a single cell

Abstract: BackgroundSingle-cell transcriptome and single-cell methylome technologies have become powerful tools to study RNA and DNA methylation profiles of single cells at a genome-wide scale. A major challenge has been to understand the direct correlation of DNA methylation and gene expression within single-cells. Due to large cell-to-cell variability and the lack of direct measurements of transcriptome and methylome of the same cell, the association is still unclear.ResultsHere, we describe a novel method (scMT-seq) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
164
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(177 citation statements)
references
References 32 publications
(37 reference statements)
3
164
0
Order By: Relevance
“…Single-cell triple omics sequencing method, including genome, DNA methylome, and transcriptome, is another innovation [117]. A complete circuit of a single cell can be detected by the integration of genomics, epigenomics, transcriptomics, and proteomics.…”
Section: Discussionmentioning
confidence: 99%
“…Single-cell triple omics sequencing method, including genome, DNA methylome, and transcriptome, is another innovation [117]. A complete circuit of a single cell can be detected by the integration of genomics, epigenomics, transcriptomics, and proteomics.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the connection strength between methylome and transcriptome varies from cell to cell. Another similar method called scMT-seq applied Smartseq 2 and scRRBS for single-cell transcriptome sequencing and methylome sequencing, respectively [103]. Compared to scM&T-seq, scMT-seq provides similar CpG islands overlap in a more cost-effective way.…”
Section: Exemplary Applicationsmentioning
confidence: 99%
“…The most critical step of simultaneously sequencing RNA and DNA is to separate RNA from DNA. The most common way is to partially lyse single cells without breaking the nucleic membrane 115,116 . The cytoplasmic mRNA is released and genomic DNA is still contained in the nuclei.…”
Section: Simultaneous Sequencing Of Dna and Rnamentioning
confidence: 99%